Development Of Local Wisdom-Based Scrapbook Media For Students' Narrative Writing Learning At Elementary School - Made Sutrisna Maha Terianita; Ni Nyoman Lisna Handayani; I Komang Surya Adnyana (Universitas Islam Ahmad dahlan, 2026)
The low narrative writing abilities of SDN 4 Tista's fourth-grade students, which are typified by challenges in coming up with ideas, creating a cohesive story structure, and using less-than-ideal word choice and writing mechanics, are what spurred this study. The goal of this research is to create a digital scrapbook medium that is grounded in local knowledge and that is reliable, useful, and efficient for teaching narrative writing. Using the Borg and Gall model, which is broken down into seven stages, the research employs the Research and Development (R&D) method. These stages include needs analysis, product design, expert validation, revision, and practicality and effectiveness trials. Twenty-four fourth-graders from SDN 4 Tista served as the research subjects. The findings demonstrated that following revision, the media received a very good category in the validity aspect. 89.4% of students met the very good criteria on the practicality test. The average student score increased from 55.47 on the pretest to 78.91 on the posttest, according to the effectiveness test. Therefore, the local wisdom-based digital scrapbook works well to help elementary school pupils become better storytellers.